(untitled) (Comillas Journal of International Relations, 2020)
This study is framed into research-action project. Its main goal is to incorporate in the areas of knowledge of future graduates the message of the United Nations 2030 Agenda with the aim of assimilate it and, thus, encourage students to incorporate it into their professional or work activity. The methodology used to carry out the activity is flipped classroom. We consider that it is the most appropriate methodology for students to delve into the issues that the planet faces, to be aware of them and, consequently, acquire the necessary skills that allow them to provide solutions. The research team is made up of professors who teach in three different areas of knowledge attached to the Faculty of Social Sciences and Communication of the European University of Madrid. The Research Project is multidisciplinary in nature, having been applied in five different subjects, which, in turn, are taught in four different degrees. The results obtained through the survey carried out show that 85.83% of the students have a high degree of satisfaction with the activity on a global level and that they highly value the skills developed in the activity.